The Matrix Verb as a Source of Comprehension Difficulty in Object Relative Sentences. (4th November 2016) - Staub, Adrian; Dillon, Brian; Clifton, Charles
Abstract: Two experiments used eyetracking during reading to examine the processing of the matrix verb following object and subject relative clauses. The experiments show that the processing of the matrix verb following an object relative is indeed slowed compared to the processing of the same verb following a subject relative. However, this difficulty is entirely eliminated if additional material intervenes between the object gap and the matrix verb. An explanation in terms of spillover processing is ruled out, suggesting that it is the gap‐matrix verb sequence that is itself responsible for the difficulty. We consider two accounts of this difficulty, one emphasizing the potential difficulty of rapidly switching between the sentential subject's thematic or syntactic role in the embedded clause and its role in the matrix clause, and one emphasizing the potential difficulty of performing two demanding memory retrievals in rapid succession. The present experiments also closely replicate the previous findings from eyetracking that the noun phrase and the verb within an object relative are both loci of processing difficulty, but that the former induces substantially greater difficulty.